2013
DOI: 10.1371/journal.pone.0063208
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Mitochondrial DNA Content in Association with Exposure to Polycyclic Aromatic Hydrocarbons in House Dust during Wintertime: From a Population Enquiry to Cell Culture

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widespread environmental pollutants that are formed in combustion processes. At the cellular level, exposure to PAHs causes oxidative stress and/or some of it congeners bind to DNA, which may interact with mitochondrial function. However, the influence of these pollutants on mitochondrial DNA (mtDNA) content remains largely unknown. We determined whether indoor exposure to PAHs is associated with mitochondrial damage as represented by blood mtDNA content. Blood mtDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 41 publications
(42 reference statements)
9
40
1
2
Order By: Relevance
“…Indeed, tobacco smoke consists of large amounts of particulate matter. Lung32 and systemic inflammation, prothrombotic reactions,33 modulations in heart rate variability34 and blood pressure,35 are mechanisms which explain the association between AMI and particulate air pollution29 at concentrations which are much lower than exposure to second-hand smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tobacco smoke consists of large amounts of particulate matter. Lung32 and systemic inflammation, prothrombotic reactions,33 modulations in heart rate variability34 and blood pressure,35 are mechanisms which explain the association between AMI and particulate air pollution29 at concentrations which are much lower than exposure to second-hand smoke.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the mitochondrial DNA content, we determined the ratio of one mitochondrial gene to a nuclear gene using quantitative real-time RT-PCR as described previously with some modifications (Pieters et al 2013). Total DNA was extracted using the DNeasy Blood and Tissue Kit (Qiagen) following the manufacturer's instructions (Quick-Start Protocol).…”
Section: Mitochondrial Dna Contentmentioning
confidence: 99%
“…In addition, induction of mitochondrial CYP1A enzyme activity is observed in killifish following benzo(a)pyrene exposure (Jung and Di Giulio, 2010), and it has been demonstrated that bulky DNA adducts formed by PAH metabolites interact with mtDNA (Jung et al, 2009). Furthermore, exposure to PAHs in mammals is associated with effects on nDNA and mtDNA, changes in membrane potential, induction of apoptosis, decreases in ATP production, mitochondrial morphological changes and structural damage, and oxidative stress (Backer and Weinstein, 1980; Graziewicz et al, 2004; Li et al, 2003; Pavanello et al, 2013; Pieters et al, 2013; Xia et al, 2004; Zhu et al, 1995). …”
Section: Introductionmentioning
confidence: 99%